Calculating the Variation of the Universal Parameter (Variable) Using Kepler’s Equation for Different Orbits - Ibrahim, Rasha H. (Iraqi Journal of Science, 2025)
Stumpff functions are an infinite series that depends on the value of z. This value results from multiplying the reciprocal semi-major axis with a universal anomaly. The purpose from those functions is to calculate the variation of the universal parameter (variable) using Kepler’s equation for different orbits. In this paper, each range for the reciprocal of the semi-major axis, universal anomaly, and z is calculated in order to study the behavior of Stumpff functions C(z) and S(z). The results showed that when z grew, Stumpff functions for hyperbola, parabola, and elliptical orbits were also growing. They intersected and had a tendency towards zero for both hyperbola and parabola orbits, but for elliptical orbits, Stumpff functions exhibited unstable behavior, with distinct, insignificant peaks disappearing as z increased. In comparison to other published studies in this section, the results showed good agreement.